Anxiety levels and wild running susceptibility in rats: assessment with elevated plus maze test and predator odor exposure - de Paula, HMG; Gouveia, A.; de Almeida, M. V.; Hoshino, K. (Elsevier B.V., 2005)
It is reported in the literature that nearly 20% of rats are susceptible to displays of wild running (WR) behavior when submitted to high intensity acoustic stimulation. Some characteristics of WR suggest that it can be viewed as a panic-like reaction. This work aimed to test whether WR-sensitive rats show higher levels of anxiety in elevated-plus-maze (EPM) and predator-odor exposure paradigms in comparison with WR-resistant ones. Male adult Wistar rats were submitted to two trials of acoustic stimulation (104 dB, 60 s) in order to assess WR susceptibility. Seven WR-sensitive and 15 WR-resistant rats were evaluated by the EPM test. Other 13 WR-sensitive and 18 WR-resistant animals were submitted to the predator-odor exposure test which consisted of a 10 min-session of free exploration in a specific apparatus containing two odoriferous stimuli: cotton swab imbedded with snake cloacal gland secretion or with iguana feces (control). WR-sensitive rats presented a significantly higher closed-to open-ann-entry ratio in the EPM test. All rats responded with anxiety-like behaviors to the predator odor exposure, although the WR-sensitive ones showed a marked behavioral inhibition regardless of the odor condition. We conclude that WR-sensitive rats present elevated levels of anxiety manifested by means of passive behavioral strategies. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: anxiety; elevated-plus maze; panic; predator odor; rat; wild running